Association between β-blocker dose and cardiovascular outcomes after myocardial infarction: insights from the SWEDEHEART registry. Issue 4 (1st September 2020) - Mars, Katarina; Wallert, John; Held, Claes; Humphries, Sophia; Pingel, Ronnie; Jernberg, Tomas; Olsson, Erik M G; Hofmann, Robin
Abstract: Aims: Dose-dependent effects of β-blockers on survival and cardiovascular outcomes after myocardial infarction (MI) are not well understood. We investigated the long-term risk of cardiovascular events in patients with different doses of β-blockers after MI. Methods and results: This was a nationwide observational study linking morbidity, mortality, socioeconomic, and medication data from Swedish national registries. Between 2006 and 2015, 97 575 unique patients with first-time MI were included. In total, 33 126 (33.9%) patients were discharged with ≥50% of the target β-blocker dose and 64 449 (66.1%) patients with <50% of the target β-blocker dose used in previous randomized trials. The primary composite endpoint was re-infarction or all-cause death within 1 year from discharge. Multivariable adjusted 1-year follow-up estimates using mixed effects Cox regression [HR (95% CI)] showed that patients treated with ≥50% of the target dose had a similar risk of the composite endpoint [1.03 (0.99–1.08)] and a somewhat higher risk when stroke, atrial fibrillation, or heart failure hospitalization were added to the composite endpoint [1.08 (1.04–1.12)], compared with patients on <50% of the target β-blocker dose. Results remained similar up to 5 years of follow-up and consistent across relevant patient subgroups, including patients who developed heart failure during the index hospitalization. Conclusions: In contrast to doses of β-blockers used in previous trials, ≥50% of the target β-blocker dose was not associated with superior cardiovascular outcomes up to 5 years as compared with <50% of the target dose. Contemporary randomized clinical trials are needed to clarify the optimal dose of β-blockers after MI.